Demographic Structure and Macroeconomic Trends - Yunus Aksoy; Henrique S. Basso; Ron P. Smith; Tobias Grasl (Center for Economic Studies and ifo Institute (CESifo), 2016)
The effect of changes in demographic structure on medium-run trends of key macroeconomic variables is estimated using a Panel VAR of 21 OECD economies. The panel data variability assists the identification of direct effects of demographics, while the dynamic structure uncovers long-term effects. Young and old dependants are found to have a negative impact while workers contribute positively. We propose a theoretical model, highlighting the relationship between demographics, innovation and growth, whose simulations match our empirical findings. The current trend of population aging and reduced fertility is found to reduce output growth and real interest rates across OECD countries.
Keywords: E32; J11; 330; population age profile; medium-term; output growth; innovation; life-cycle; Kuznets cycles